PENGARUH TAX PLANNING, UKURAN PERUSAHAAN, CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP MANAJEMEN LABA - Desifa Kurnia Santi; Dewi Kusuma Wardani (Jurnal Akuntansi, 2018)
This study aims to determine the effect of tax planning, firm size, and corporate social responsibility (CSR) to earnings management. This research is causality. Population in this research is manufacturing company of food and beverage subsector that listed in BEI during period of 2012 until 2016. The sample in this study was determined based on purposive sampling which resulted 8 samples of company. The type of data used is secondary data obtained from www.idx.co.id. Data analysis technique used is multiple linear regression analysis. The result of multiple regression test shows that the tax planning, company size, and corporate social responsibility (CSR) simultaneously affect the earnings management and the three independent variables influence 62.5% to the dependent variable while the rest is influenced by other factors outside the research variables. Partially, tax planning has no effect on earnings management with t count smaller than t table that is equal to 1.449 <1.68830 and significance value 0.156> 0.05, firm size negatively affect earnings management with t count equal to -7.853 and significance level 0.000, and corporate social responsibility (CSR) have a positive effect on earnings management with t arithmetic of 2.784> t table of 1.68830 with significance 0.008 <0.05. Keywords: tax planning, company size, corporate social responsibility (CSR), earnings management